2022
DOI: 10.7717/peerj.13994
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression profile analysis of the SnRK2 gene family in cucumber

Abstract: The sucrose non-fermenting-1-related protein kinase 2 (SnRK2) is a plant-specific type of serine/threonine protein kinase that plays an important role in the physiological regulation of stress. The objective of this study was to identify and analyze the members of the SnRK2 gene family in cucumber and lay a foundation for further exploration of the mechanism of CsSnRK2 resistance to stress. Here, 12 SnRK2 genes were isolated from cucumber and distributed on five chromosomes, phylogenetic clustering divided the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…The classification of the three gene families agrees with previous phylogenetic analyses in Arabidopsis, Brassica rapa , rice, tomato, banana, or cucumber [ 20 23 , 28 , 30 , 31 , 46 , 47 , 49 , 61 ]. Gene structure and protein motifs were also found to be conserved within members of the same family in C. sativus , rice and Gossypium ssp.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The classification of the three gene families agrees with previous phylogenetic analyses in Arabidopsis, Brassica rapa , rice, tomato, banana, or cucumber [ 20 23 , 28 , 30 , 31 , 46 , 47 , 49 , 61 ]. Gene structure and protein motifs were also found to be conserved within members of the same family in C. sativus , rice and Gossypium ssp.…”
Section: Discussionsupporting
confidence: 87%
“…PYLs , PP2Cs and SnRK2s are encoded by multigene families with a variable number of genes among species. The number of CpPYL and CpSnRK2 genes in C. pepo (19 and 10, respectively) is similar to that of Arabidopsis (14 and 10) or cucumber (14 and 11) [ 23 , 46 , 49 ]. However, the number of CpPP2C genes was higher in C. pepo (102) than in Arabidopsis (80) or cucumber (56) [ 28 , 58 ], which is probably associated with duplication of the whole genome in Cucurbita [ 56 , 59 ], but also with the evolutionary diversification of the PP2C gene family to adapt plant species to multiple environments [ 28 , 60 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that CYPC‐type GRX genes mainly encode detoxification and stress‐responsive proteins, while CGFS‐type GRX genes have protective effects against oxidative stress and are ubiquitous in diverse organisms (Li et al . 2007; Wan 2014). CC‐type GRX genes are unique to land plants and occur in much larger numbers than other types of GRX genes.…”
Section: Discussionmentioning
confidence: 99%
“…The FAR1/FHY3 protein sequences of cucumber, Arabidopsis and tomato were downloaded from the online database Ensembl [20]. The MEGA11 software (v2.010) was used to construct a phylogenetic tree of 61 FAR1/FHY3 protein sequences by applying the Maximum Likelihood method [25]. The bootstrap replication value was set as 1000, and the other parameters remained constant.…”
Section: Phylogenetic Analysis Of Cucumber Far1/fhy3 Genesmentioning
confidence: 99%